Public accounts committee (PAC) of a Malaysian state: An exploratory analysis - Samsudin, Rose Shamsiah; Mohamed, Nafsiah (2010)
Of the three legislature's functions, unlike representation and law-making, oversight is particularly related to PACs. As a strong committee of legislature, PACs can emerge as a potential structural solution to the need of the State Legislative Assemblies (SLAs) to monitor the financial conducts of the state governments. However, to do so, studies have suggested that PACs' institutional designs and capacity building are among factors to be improved to promote PACs' effectiveness. Within Malaysian PACs context, much about the related situations is not known for sure due to lack or limited exploration on the matter. Thus, besides attempting for an exploration of PAC practices in general, one of the Malaysian state government's PAC institutional settings and capacity are explored in order to illuminate the state of affairs. Generation of data to address the topic understudy is based on interviews, observation and also use of documents. Such information gives this research a knowledge base to launch further inquiries into future research initiatives regarding the topic.